Selvagens na igreja a frisa de Saint-Jacques de Dieppe: um caso de bricolagem cultural - Del Priore, Mary Lucy Murray (Revista de História, 1995)
This article discusses the cultural relationships between France and Brazil during the sixteenth century through the images of Indians and Americans.